2018
DOI: 10.1177/0310057x1804600304
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Haemodilution with Succinylated Gelatin Solution on Coagulation in Vitro as Assessed by Thromboelastometry and Impedance (Multiple Electrode) Aggregometry

Abstract: We investigated the in vitro viscoelastic changes of progressive haemodilution with succinylated gelatin (SG) solution compared with normal saline (NS) using rotational thromboelastometry (ROTEM®). Whole blood (WB) samples obtained from 20 healthy volunteers were diluted in vitro with SG solution or NS by 10%, 20% and 40%. Fibrinogen concentration and ROTEM (EXTEM, FIBTEM) variables including coagulation time (CT), clot formation time (CFT), α-angle, and maximum clot firmness (MCF) were measured in the undilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
4
8
0
2
Order By: Relevance
“…On the other hand, the CFT of all reagents was increased already after 20% dilution. These results are in line with previous reports and indicate that 20% dilution does not yet affect the initiation of coagulation (CT), but prolongs already the time to create a solid clot of 20 mm strength (CFT) [ 29 , 30 , 31 ]. Since the CFT, contrary to the CT, is highly dependent on sufficient platelet aggregation, these results indicate that hemodilution might have affected the concentration of platelets and their function [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the CFT of all reagents was increased already after 20% dilution. These results are in line with previous reports and indicate that 20% dilution does not yet affect the initiation of coagulation (CT), but prolongs already the time to create a solid clot of 20 mm strength (CFT) [ 29 , 30 , 31 ]. Since the CFT, contrary to the CT, is highly dependent on sufficient platelet aggregation, these results indicate that hemodilution might have affected the concentration of platelets and their function [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to similar dilutions with crystalloid, in vitro dilutions (10%, 20%, and 40%) of human whole blood with succinylated gelatin cause a greater increase in CFT and greater decrease in alpha angle and MCF on ROTEM, particularly at a 40% dilution (77). Similar concentration-dependent changes have been demonstrated with TEG (123,124).…”
Section: Gelatinsupporting
confidence: 57%
“…Functional platelet studies have demonstrated a reduction in platelet adhesion and activation, as evidenced by prolonged PCT (21,38), although not all studies consistently show this effect. Although gelatin interferes with ristocetin-induced aggregation (66,67,(73)(74)(75), it mostly fails to impair aggregation stimulated by other agonists (66,(76)(77)(78)(79)(80). The effect of gelatin on PCT is also mixed between species (64,81).…”
Section: Mechanisms Of Hypocoagulabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Уменьшение плотности тромба на 5-й, 10-й, 15-й минуте после достижения точки желирования и максимальной плотности тромба (МА или MCF) по данным ротационной тромбоэластометрии (РОТЭМ) и тромбоэластографии (ТЭГ), используется как диагностический маркер коагулопатии [26]. Гемодилюционная коагулопатия выявляется достоверно РОТЭМ и ТЭГ по снижению плотности тромба в точке на 10-й минуте и МА при разведении на 33-40% изотоничными кристаллоидными растворами [9,[27][28][29] и при 20-35% разведении препаратами желатина [30]. В этих точках отмечена сильная корреляция между плотностью тромба и концентрацией фибриногена.…”
Section: Groupunclassified